(untitled) (Nóema, 2023)
Antonio Gramsci was a philosopher capable of making an original and valuable contribution to the field of Marxism. The intent of this paper is to investigate the conception of philosophy present in the work of the Sardinian author and its connection with the educational institution, in a framework in which the relationship between structure and superstructure is deepened and elaborated away from mechanistic schemes as thought and consciousness assume relevance in the progress toward human liberation. The redefinition of the philosophical discipline will follow from a general reconsideration of the relationship between matter and thought, two aspects co-equal to the same dimension, and will involve a revision of the notions of reality, inextricably linked to man’s concrete workings, and truth, a term that in this context takes on strong political connotations. An important parenthesis will be devoted in this regard to intellectuals as mediators between class and political power. The school will then be analyzed so as to highlight its revolutionary potential as a place of formation of consciousness and personality.